Genetic Basis of Diabetic Nephropathy - Kalra, O.P. (Annals of the National Academy of Medical Sciences (India), 2017)
It is well known that all patients with Type 2 Diabetes Mellitus (T2DM) do not develop chronic kidney disease (CKD). Several metabolic, hemodynamic and intracellular mechanisms have been proposed to play role in the pathogenesis of Diabetic Nephropathy (DN). Clustering of patients with DN in certain ethnic groups and families suggests the role of genetic factors. We have studied various facets about genetic determinants which may influence the development of kidney disease in patients with T2DM.We have found that Angiotensin Converting Enzyme (ACE) DD genotype conferred the maximum risk, whereas ACE II genotype seemed to confer protective role against development of diabetic and nondiabetic CKD. Further, we found that oxidative stress (OS) plays a significant role in the development of DN and that Glutathione S-transferase theta-1and/or Glutathione S-transferase Mu-1 null genotypes are associated with higher OS in patients with DN. In addition, we also found that increased levels of inflammatory mediators, i.e. Tumor necrosis factor-α (TNF-α), high-sensitivity Creactive protein (hsCRP) and Urinary Monocyte Chemoattractant Protein-1 (uMCP-1) play a significant role in contributing to OS. We have shown that genetic polymorphism of NF-kB gene and TNF-α gene plays a role in determining serum level of various inflammatory markers and oxidant stress parameters. We found significant association of -429T/C and Gly82Ser Receptors for Advanced Glycation End-products (RAGE) polymorphisms with the development of macrovascular and microvascular complications, respectively in T2DM subjects. Further, we have observed that AGEmediated exacerbation of RAGE expression may play a role in pathogenesis of various vascular complications in T2DM.To conclude, polymorphisms of various genes involved in renin-angiotensin aldosterone system (RAAS), inflammatory, oxidant stress, cytoprotective and nitrous oxide pathways and enhanced RAGE mRNA expression may adversely influence final common pathway through oxidant stress mechanisms, and influence the levels of various cytokines and intracellular signaling mechanisms, thereby influencing the susceptibility of patients with diabetes mellitus for development of kidney disease and vascular complications.
Keywords: Diabetic nephropathy; genetic factor; chronic disease